Biofloc and green water condition improves reproductive traits and fatty acid composition of Artemia franciscana cultured under limited algal conditions. Issue 1 (29th November 2022) - Ogello, Erick O.; Outa, Nicholas O.; Mukaburu, Bramwel O.; Muthoka, Mavindu
Abstract: This study investigated the effect of biofloc and green water conditions on the survival, growth, reproductive traits, and fatty acid composition of the brine shrimp Artemia franciscana . Artemia was cultured in glass jars using three replicated treatments, that is, Control (7.0 × 10 6 cells ml −1 of freshly cultured Tetraselmis tetrathele ), green water technology—GWT (control + 0.5 g/L of chicken manure extract [CME]) and biofloc technology—BFT (GWT + molasses). Artemia cysts were hatched and batch cultured in a 1‐L glass jar containing 500 ml of natural seawater, stocked at 2 nauplii/ml. In the first 2 days, Artemia was fed with fresh T. tetrathele for conditioning, after which each treatment was applied daily until the end of the experiment. Artemia cultures were maintained at 28.0 ± 1°C using an electrically heated water bath system with constant aeration and light (2000 lux) for 30 days. There was higher Artemia survival in BFT (91.3 ± 3.2%) cultures than GWT (78.1 ± 2.9%) and Control (66.8 ± 1.3%). Female pre‐reproductive period (days) was longer (25 ± 0.5) in control than in GWT (21.8 ± 0.7) and BFT (19.6 ± 0.6), while reproductive period (days) was longer in BFT (20.9 ± 2.6) than GWT (16.4 ± 2.3) and Control (12.8 ± 1.9). Total broods per female per day were higher in BFT (4.3 ± 0.3) than in GWT (3.5 ± 0.2) and Control (2.5 ± 0.3). BFT enhanced the ovoviviparous reproduction cycle with higher total offspring per female (73.5 ± 6.1) than GWT (66.2 ± 7.9) and Control (42.6 ± 12.1). BFT‐cultured Artemia had higher concentrations of myristic acid, oleic acid, palmitic acid, linoleic acid, and arachidic acid. Better Artemia reproductive and nutritive traits in BFT conditions could have been enhanced by the combination of nutritious biofloc and algal materials. BFT and CME promise a major leap towards developing a nutritionally rich diet for Artemia . Abstract :